SOURCES OF RAW MATERIALS FOR OBTAINING HIGH MOLECULAR WEIGHT COMPOUNDS (Web of Technology: Multidimensional Research Journal, 2025)
Today, without exaggeration, the importance of the chemical industry in the development of our country's economy is growing. One of the characteristic features of the modern chemical industry is the rapid growth of organic synthesis. One of the important tasks of the development of the chemical industry is the full use of the achievements of modern chemistry in all branches of industry and life, the production of new, more advanced and cheaper means of production and consumer goods.